EDUCATIONAL TECHNOLOGIES AS A TOOL OF ENHANCING THE PROCESS QUALITY OF THE PERSONALITY DEVELOPMENT - Blagun, Nataliya (Mountain School of Ukrainian Carpaty, 2018)
The main task of the article is to define the concept of «educational technologies» in the context of modern educational space. The system of views of domestic and foreign scholars is revealed. It defines educational technology as an integration model, integrates into a holistic system of purpose, change, didactic complex. The main emphasis is on progressive educational technologies, especially: personally oriented, projective, cooperative, simulation, informational. It has been established that the highest result in learning is achieved by students under the following conditions: the formation of an active attitude to teaching, the teaching of material in a certain sequence, demonstration and consolidation while exercising various methods of mental and practical activity, the application of knowledge in practice. The theoretical component of pedagogical technology is the concept as a system of views on a particular phenomenon. In modern theory and practice, the most common are person-oriented technologies based on the theory of personality-oriented learning, the central figure of which stands for the personality, identity and self-worth. The subjective experience of each child is first disclosed and then is consistent with the content of education. The main factors that are laid down in pedagogical technologies and determine their fundamental difference is their basis - theory and concept. This explains their diversity, which is disclosed by domestic scientists in scientific and methodological works. It is proved that personally oriented technologies are focused on the personality of the child, providing comfortable conditions for its development, realization of its natural psychophysiological, intellectual, spiritual and spiritual instincts.